2022
DOI: 10.1002/col.22772
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric characterization of color imaging systems using a multi‐inputPSO‐BPneural network

Abstract: Most commonly used camera characterization methods do not use a deep learning‐based artificial neural network approach at present. This article proposes a colorimetric characterization method for color imaging systems based on the multi‐input particle swarm optimization backpropagation neural network. Combined with a particle swarm optimization algorithm for global search and a 19‐input vector, this method not only overcomes the effects of local extrema on the multi‐input backpropagation neural network, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…It can be seen from Formulas (1) and (2) that there exists a nonlinear conversion between the ( R , G , B ) and the ( X , Y , Z ). In fact, different methods have been used to model the conversion from the RGB space to the XYZ space [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Among them, polynomial transforms and the BP artificial neural network (BP-ANN) are the most popular.…”
Section: The Problems Of Wide Color Gamutmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen from Formulas (1) and (2) that there exists a nonlinear conversion between the ( R , G , B ) and the ( X , Y , Z ). In fact, different methods have been used to model the conversion from the RGB space to the XYZ space [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Among them, polynomial transforms and the BP artificial neural network (BP-ANN) are the most popular.…”
Section: The Problems Of Wide Color Gamutmentioning
confidence: 99%
“…Until now, different kinds of colorimetric characterization methods have been developed, including polynomial transforms [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], artificial neural networks (ANN) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], and look-up tables [ 24 ]. In 2016, Gong et al [ 12 ] demonstrated a color calibration method between different digital cameras with ColorChecker SG cards and the polynomial transform method and achieved an average color difference of 1.12 (CIEDE2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Liao and others have many meaningful articles in the field of color. 30,31 Poljicak et al 32 proposed a radial basis function (RBF) ANN for colorimetric characterization. The accuracy of colorimetric characterization can be optimized by choosing an adequate basis function.…”
Section: Introductionmentioning
confidence: 99%
“…This method greatly decreased the mathematical computation in color appearance prediction. In addition, Liao and others have many meaningful articles in the field of color 30 , 31 . Poljicak et al 32 .…”
Section: Introductionmentioning
confidence: 99%